Optimal Power Flow and Contingency Analysis with Security Considerations Using Jaya Optimization Algorithm (The International Journal of Engineering & Information Technology (IJEIT), 2025)
Optimal power flow (OPF) is one of the fundamental tasks in modern complex electric grid operation. Its objective is to improve the economic and secure coordination on electrical networks based on pre-defined constraints. Combined with a complex operational network and higher demand patterns at times of day / week, it is clear that OPF solutions need to be accurately designed. This accuracy is crucial in order to increase stability across networks over time which in turn will reduce future operational risk. While modern grids increasingly integrate renewables, this work focuses on conventional OPF to establish Jaya’s core efficacy for contingency management, providing a foundation for future renewable integration. This paper presents a computationally distinct application of the Jaya optimization algorithm for solving OPF problem taking into account contingency analysis and security assessment. It then proceeds to carry out an optimization using the Jaya algorithm, a cost-effective and parameter-less-dependent technique for system-wide minimization of operational costs with adherence constraints imposed on online security and stability. The suggested approach integrates contingency analysis into risk assessment in order to assess critical vulnerabilities of networks and determine how potential failures propagate. Results of the simulation prove that Jaya algorithm outperforms GA and PSO in optimization. The proposed method not only increases the security level of OPF but it is also human-friendly rather than computationally expensive, making it an appropriate solution for real-time application of OPF schemes.